Aortic compliance variation in long male distance triathletes: A new insight into the athlete`s artery? - Dupont, A.-C.; Poussel, M.; Hossu, G.; Marie, P.-Y.; Chenuel, B.; Felblinger, J.; Mandry, D. (Journal of Science and Medicine in Sport, 2017)
Objectives: To assess cardiac and vascular adaptations in long-distance male triathletes and the influence of an increased training volume on these parameters. Design: Case-control study using long-distance male triathletes (Tri) (n = 12) and an age-matched cohort of sedentary volunteers (Ctrl). Methods: All participants gave an informed consent and underwent a Cardiovascular Magnetic Resonance imaging (CMR) exam to measure left and right ventricle functional parameters, and aortic parameters (surface, strain, compliance, pulse wave velocity). This exam was repeated in the triathletes` group after an increased training volume of at least 2 h/week for six weeks. Results: Compared to control volunteers, triathletes presented at baseline a typical pattern of athlete`s heart (higher end-diastolic, end-systolic and stroke volumes index, p = 0.009, and lower cardiac rate, p = 0.015) but similar vascular characteristics except a trend towards an enlarged ascending aorta (surface 942 ± 106 vs 812 ± 127 mm2, p = 0.058). Between the two visits, the triathletes increased their weekly training time from 9.67 ± 2.43 (Tri1) to 12.15 ± 3.01 h (Tri2): no modifications were found regarding cardiac parameters, but compliance and distensibility of the ascending aorta increased, from 2.60 to 3.34 mm2/mmHg (p = 0.028) and from 3.36 to 4.40 × 10-3 mmHg-1 (p = 0.048) respectively. Conclusions: Using CMR, we showed that vascular characteristics of the ascending aorta may vary along the sport season in endurance athletes. This remodelling could be considered as a physiological adaptation, but could eventually lead to an adverse vascular remodelling.